A LIVING CURRICULUM: CONVERSATIONS ABOUT LEARNING AND TEACHING - Marshall, Steven; Wilson, Scott (Journal of Technical Education and Training, 2012)
Unitec New Zealand’s ‘Living Curricula’ is both an Academic Strategy and an aspiration for a unique institutional culture. The Department of Performing and Screen Arts has developed course curriculum that crosses discipline boundaries and exploits collaborative opportunity to leverage economical solutions to ever-growing sector and system constrains. Developing a living curricula involves ‘conversations’ about enquiry, knowledge, practice, and learning and teaching approaches which focus on engagement between and among learners, teachers, practitioners, communities, scholars, and with self and texts. It involves tailored teaching & learning approaches that are defined by four key ideas: • Enquiry (how learners go about asking and answering questions); • Discipline (how learners engage with the knowledge that underpins the discipline); • Autonomy (how learners increasingly develop their capability and confidence); and • Conversation (how learners engage with self and others to develop understandings). Embedded within a ‘living curricula’ is the concept of Ako, a Maori word which means to learn study, instruct, and teach or advice. Ako describes a teaching and learning relationship where the educator is also learning from the student and where educators’ practices are informed by the latest research and are both deliberate and reflective. The key aspects of ako are: • Language, identity and culture counts – knowing where students come from and building on what students bring with them. • Productive partnerships – Students, whÄnau (extended family) and educators sharing knowledge and expertise with each other to produce better outcomes. A ‘living curricula’ is not forever changing it is simply alive!